Effects of Osteoporosis‐Inducing Drugs on Vitamin D‐Related Gene Transcription and Mineralization in MG‐63 and Saos‐2 Cells. Issue 5 (20th May 2016) - Wegler, Christine; Wikvall, Kjell; Norlin, Maria
Abstract: Vitamin D3 is important for calcium and phosphate homeostasis. To exert its effects, vitamin D3 has to be enzymatically activated into 1, 25D3 (1, 25‐dihydroxyvitamin D3 ). Regulation by endogenous vitamin D metabolites of the activation and inactivation of 1, 25D3 is important to maintain adequate amounts of active vitamin D3 . Vitamin D deficiency and low bone mineral density have been linked to treatments with antiretroviral drugs and glucocorticoids. However, the causes of drug‐induced osteoporosis remain unclear. The antiretroviral drugs efavirenz and ritonavir as well as the glucocorticoid dexamethasone were included in this study. Their effects on transcription of vitamin D‐regulating enzymes in MG‐63 cells were investigated. Ritonavir and dexamethasone both induced transcription of CYP27B1, the enzyme responsible for the formation of 1, 25D3 . Efavirenz, however, suppressed CYP27B1 expression. When administered together with endogenous vitamin D metabolites, dexamethasone and efavirenz counteracted the 1, 25D3 ‐mediated up‐regulation of CYP24A1, which inactivates 1, 25D3 . This suggests that the drugs may interfere with local regulation of the vitamin D metabolizing system in osteoblasts. Studies on mineralization were performed in MG‐63 cells and Saos‐2 cells by measuring calcium concentrations accumulated over time. The effects of efavirenz, ritonavir and dexamethasone and/or vitamin D metabolites were examined. 1, 25D3 induced mineralization in both cell lines. Efavirenz administered alone did not affect mineralization but suppressed the inducing effects of 1, 25D3 on mineralization in both MG‐63 cells and Saos‐2 cells. In summary, the results suggest that antiretroviral drugs and glucocorticoids may adversely affect bone by interference with the vitamin D system in osteoblasts.